Many Socrates: An Introduction to the Voices of the Socratic circle - Illarraga, Rodrigo; Lozano Nembrot, Milena (Revista Archai, 2021)
This paper aims to introduce the plurality of voices that encircle the character of Socrates as a philosophical issue. A universe of criticism and praise, constant dialogues of answers and replicas that we can trace back to Socrates' Accusations against Polycrates and the answers of Xenophon and Plato in their apologies. In these interstices we can reconstruct not only the figure of Socrates, but also the dynamics of his circle an extensive and diverse group marked both by the differences between them and their devotion to their friend and teacher This is precisely the question that runs through the dossier. After an introduction on the subject and, specially, on the role of Xenophon’s works, the dossier’s papers will be described, showing the common topics and reflections.